Riesgo de enfermedad coronaria determinado por la escala de Framingham en pacientes adultos mayores de la ciudad de Machala, 2014 - Naranjo Romero, Ralph Russell (2015)
The objective of the study is to stratify the risk of coronary heart disease to Table of Framingham, describe the individual characteristics determine the levels of total cholesterol and HDL, the frequency of hypertension, identify the main comorbidities to develop coronary heart disease in older adults the city of Machala. 2014. Type of study was cross-sectional, was performed on 388 elderly belonging to the Golden Spike Group subsidiary Teofilo Davila Hospital in coordination with the Provincial Government of El Oro and MIES, Framingham Table applies where 120 patients (30.56 %) have low risk, followed by 78 patients (19.68%) have a moderate risk, have a moderately high risk 23.31% (90 people) and 26.43% (100 people) are at high risk of developing coronary heart disease within 10 years.